STRATEGI NABAWI DALAM MENDIDIK GENERASI: ANALISIS KUALITATIF TERHADAP KONSEP TADARRUJ DALAM HADIS BUKHARI - Mirhabun Nadir; Muhammad Ilmi Najib; Mahmudi, Rois; Damiri, Adam (LPPM STAI Muhammadiyah Probolinggo, 2025)
This research aims to analyze in depth the educational strategy of the Prophet Muhammad SAW in the hadith narrated by Bukhari, with a focus on the pedagogical meaning of the concept of tadarruj or stages of imparting knowledge as contained in the words